2006
DOI: 10.1089/pho.2006.24.715
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage of Class V Glass Ionomer Restorations after Conventional and Er:YAG Laser Preparation

Abstract: The application of Ketac Fil Plus to laser-prepared enamel and dentin resulted in a better and more reproducible seal compared to conventionally prepared tooth surfaces. When using the more viscous Fuji IX application, Er:YAG lasing did not improve marginal adaptation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
3
16
0
1
Order By: Relevance
“…With the three-step etch-and-rinse adhesive system, the increase in procedural steps posed a greater technique sensitivity, which might result in incomplete penetration of resin in the demineralized dentin surface 43) . Both adhesive systems have good resin monomer penetration capability, but remaining water in the water-based system (Scotchbond Multi-Purpose Plus) might hamper resin penetration/polymerization 44) . This explained why Adper Single Bond exhibited better microleakage performance than Scotchbond Multi-Purpose Plus in this study, although not with a significant difference (p>0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the three-step etch-and-rinse adhesive system, the increase in procedural steps posed a greater technique sensitivity, which might result in incomplete penetration of resin in the demineralized dentin surface 43) . Both adhesive systems have good resin monomer penetration capability, but remaining water in the water-based system (Scotchbond Multi-Purpose Plus) might hamper resin penetration/polymerization 44) . This explained why Adper Single Bond exhibited better microleakage performance than Scotchbond Multi-Purpose Plus in this study, although not with a significant difference (p>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…No statistically significant differences in microleakage were found between these two cavity preparation methods 67) . Delme et al 44) also investigated the effects of Er:YAG laser and diamond bur on microleakage in human teeth in vitro. With Class V cavities prepared with a laser or a bur at 1.5 mm below the enamel-cement junction, no statistically significant differences in microleakage were found between these two cavity preparation methods 44) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies used CO 2 and Nd:YAG lasers and found that these lasers may improve the bond strength or adaptation of glass ionomers, 23,24 but other studies that used Er:YAG laser energy showed that laser irradiation may increase or decrease the sealing or bond strength of glass ionomers. 1,28,29,30 In view of the increasing interest in the use of lasers in dental practice, and due to research on the influence of the use of Er,Cr:YSGG laser energy for surface treatment in bonding of glass ionomer restorations, the aim of this in vitro study was to assess the amount of bond strength in dentin surfaces conditioned and restored with one conventional and two resin-modified glass ionomer cements.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have investigated Er:YAG laser treatment for caries in terms of pulp safety, restoration compatibility, water spray, output power, and pulse rate. [2][3][4][5] However, most of these studies used healthy teeth, and studies on carious teeth are lacking.…”
mentioning
confidence: 99%